2001
DOI: 10.1046/j.1526-4610.2001.041007720.x
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia and Cerebellopontine‐Angle Lipoma in a Child

Abstract: Trigeminal neuralgia and cerebellopontine-angle lipomas are very rare in children. We describe the history and findings of an 8-year-old boy with right trigeminal neuralgia and a lipoma detected by magnetic resonance imaging at the level of the root-entry zone of the right seventh cranial nerve. We propose a possible mechanism of infiltration of the trigeminal rootlets by the lipoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…20 Trigeminal neuralgia has also been associated with lipomas in children. 21 Glossopharyngeal neuralgia arises due to various causes such as tumor , infection , Chiari I malformation, infarction, dissection of the vertebral artery or neurovascular compression. 22 Childs et al have reported a case of GN in a 13 year old girl which was caused due to looping of the posterior inferior cerebellar artery.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…20 Trigeminal neuralgia has also been associated with lipomas in children. 21 Glossopharyngeal neuralgia arises due to various causes such as tumor , infection , Chiari I malformation, infarction, dissection of the vertebral artery or neurovascular compression. 22 Childs et al have reported a case of GN in a 13 year old girl which was caused due to looping of the posterior inferior cerebellar artery.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…25 Raieli et al administered carbamazepine (15 mg/ kg/day) to an 8-yearold patient suffering from trigeminal neuralgia with good results. 21 A case of trigeminal neuralgia in a 12-year-old female was controlled using gabapentin (1,200 mg/day) in combination with carbamazepine (800 mg/day). 7 Besides anticonvulsants, high dose courses of amitriptyline, phenytoin, baclofen, sodium valproate, sumatriptan, and acyclovir, together with a three day course of methylprednisolone have also been tried.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Trigeminal neuralgia (TGN) is extremely rare in paediatric populations in comparison with older ages [1,2]. Venous compression is usually the main cause of paediatric TGN.…”
Section: Introductionmentioning
confidence: 99%
“…Venous compression is usually the main cause of paediatric TGN. Additionally neoplasms or benign mass lesions in the cerebellopontine angle (CPA) may lead to TGN [1]. Carbamazepine is the first-choice medical treatment but it may not provide durable pain relief [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation